2018
DOI: 10.1371/journal.pone.0207399
|View full text |Cite
|
Sign up to set email alerts
|

Combination of triapine, olaparib, and cediranib suppresses progression of BRCA-wild type and PARP inhibitor-resistant epithelial ovarian cancer

Abstract: PARP inhibitors target BRCA mutations and defective homologous recombination repair (HRR) for the treatment of epithelial ovarian cancer (EOC). However, the treatment of HRR-proficient EOC with PARP inhibitors remains challenging. The objective of this study was to determine whether the combination of triapine (ribonucleotide reductase inhibitor), cediranib (vascular endothelial growth factor receptor tyrosine kinase inhibitor), and the PARP inhibitor olaparib synergized against BRCA wild-type and HRR-proficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 62 publications
0
21
0
Order By: Relevance
“…We have previously demonstrated that both PEO4ip and SKOV3 cells are BRCA-wild type and olaparib-resistant in cell-based assays and in vivo 29 , 30 , 38 . We first evaluated the efficacy of the combination of DB4 and olaparib to treat PEO4ip tumor xenografts, as determined by the median survival time, in a peritoneal mouse model 38 . Mice were implanted intraperitoneally (i.p.)…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We have previously demonstrated that both PEO4ip and SKOV3 cells are BRCA-wild type and olaparib-resistant in cell-based assays and in vivo 29 , 30 , 38 . We first evaluated the efficacy of the combination of DB4 and olaparib to treat PEO4ip tumor xenografts, as determined by the median survival time, in a peritoneal mouse model 38 . Mice were implanted intraperitoneally (i.p.)…”
Section: Resultsmentioning
confidence: 99%
“…We ascertain the efficacy of the combination of DB4 and olaparib to treat SKOV3 tumor xenografts, as determined by the tumor size, in a subcutaneous (s.c.) mouse model 30 , 38 . Mice were implanted s.c. with SKOV3 cells and then treated i.p.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The intriguing rise in H2AX 24 h after H2O2 application in SKOV3 cells suggests that this line may exhibit a type of 'BRCAness'. This refers to EOC (up to 50% of HGS) that exhibit a defective phenotype of homologous recombination repair (HRR) without BRCA mutations [34,35]. Of note, SKOV3 has 3 other genes mutated involved in HRR [36].…”
Section: Discussionmentioning
confidence: 99%